Peran Mahasiswa Magang dalam Mendukung Sistem Informasi dan Kualitas Pelayanan di BPJS Ketenagakerjaan Kanwil Sumbagsel - Dewi Kartika Sari; Muhammad Agung; Putri Amanatutsani; Tia Ivanka; Ullul Is’r Mi’rz Alluaimar; Vita Rahayu Fernanda (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This article discusses the role of intern students in supporting information systems and service quality at BPJS Ketenagakerjaan, Regional Office of Southern Sumatra (Kanwil Sumbagsel). The issues examined focus on the contribution of intern students to the optimization of administration and public services, particularly in the Supervision and Inspection Division (Wasrik) and the Archives Division. This study aims to describe the forms of intern student involvement and their impact on institutional performance. The research employs a qualitative descriptive method to depict the activities and roles of students in supporting the institution’s work system. The descriptive analysis of the data indicates that intern students play a role in archive management and digitization, verification of company documents, checking participant data through the BPJS Ketenagakerjaan information system, and providing administrative support for services. This involvement contributes to improved administrative orderliness, data accuracy, work efficiency, and the development of students’ professional skills.